HERNIA AND BPH: NAVIGATING THE ROUTE FOR SURGICAL DECISION MAKING (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Benign prostatic hyperplasia (BPH) and inguinal hernia are common conditions in aging males and frequently coexist due to overlapping risk factors such as chronic straining and increased intra-abdominal pressure. The presence of both conditions presents a clinical challenge in determining optimal surgical sequencing and minimizing postoperative complications. Aim: To assess the severity of lower urinary tract symptoms (LUTS) and objective bladder outlet obstruction (BOO) parameters in patients with BPH alone compared to those with concomitant inguinal hernia, and to evaluate implications for surgical decision-making. Methods: This prospective observational study included 29 male patients aged >50 years presenting with LUTS. Patients were divided into two groups: BPH only (n=16) and BPH with inguinal hernia (n=13). Evaluation included International Prostate Symptom Score (IPSS), uroflowmetry (Qmax), post-void residual urine (PVR) measurement, and pressure-flow study where indicated. Comparative statistical analysis was performed between groups. Results: The BPH with hernia group demonstrated significantly higher mean IPSS (19 vs 12; p < 0.05) and significantly lower mean Qmax (7.8 mL/s vs 10.5 mL/s; p < 0.05) compared to the BPH-only group. Post-void residual urine volumes were comparable (60 mL vs 55 mL; p > 0.05). A higher proportion of bladder outlet obstruction was observed in the combined group (54% vs 44%), although this difference was not statistically significant (p = 0.58). Conclusion: Patients with concomitant BPH and inguinal hernia exhibit greater symptom severity and more pronounced functional obstruction compared to those with BPH alone. Comprehensive preoperative urological evaluation is essential to guide individualized surgical planning and reduce postoperative complications. Multidisciplinary decision-making between urology and general surgery is recommended.